1991
DOI: 10.1002/cne.903140313
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical demonstration of salmon GnRH and chicken GnRH‐II in the brain of masu salmon, Oncorhynchus masou

Abstract: We have recently developed sensitive and specific radioimmunoassays (RIAs) for salmon gonadotropin-releasing hormone (sGnRH) and chicken GnRH-II (cGnRH-II) and have measured the contents of both GnRHs in the rainbow trout brain. Our results showed that contents of the two GnRHs are variable among different brain regions. Therefore, in order to confirm the differential distribution of the two GnRHs by a different technique, we examined the distribution of immunoreactive sGnRH and cGnRH-II in the brain of masu s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
154
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(178 citation statements)
references
References 27 publications
22
154
1
1
Order By: Relevance
“…Furthermore, among the transgenic fish with sGnRH antisense, some AS(+) fish without sperm had no or abnormal gonadal development and lower GtH levels suggesting that inhibiting sGnRH produces completely, or partially, sterile transgenic fish. Thus, these data confirm previous studies showing that sGnRH is required for development of male gonads (Amano et al, 1991;Ashihara et al, 1995). No morphological or histological differences in ovarian development were observed among AS(+) females and controls, which suggests that further studies need to be performed to understand the role of sGnRH in female gonadal development.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, among the transgenic fish with sGnRH antisense, some AS(+) fish without sperm had no or abnormal gonadal development and lower GtH levels suggesting that inhibiting sGnRH produces completely, or partially, sterile transgenic fish. Thus, these data confirm previous studies showing that sGnRH is required for development of male gonads (Amano et al, 1991;Ashihara et al, 1995). No morphological or histological differences in ovarian development were observed among AS(+) females and controls, which suggests that further studies need to be performed to understand the role of sGnRH in female gonadal development.…”
Section: Discussionsupporting
confidence: 90%
“…. oriented rostrocaudally'') are the same as those of the GnRH neurons found in the terminal nerve population (Amano et al, 1991). Conversely, these data are consistent with the idea that expression of 5Trp 7 Leu 8 6GnRH occurs primarily in the telencephalic region in salmonids, as has been previously shown in other teleosts where in situ hybridization has been performed.…”
Section: Surprising Similarity Between 5trp 7 Leu 8 6gnrh In H Burtosupporting
confidence: 89%
“…Similarly, in situ hybridization in masu salmon (Suzuki et al, 1992), rainbow trout, and Atlantic salmon (Bailhache et al, 1994), using 5Trp 7 Leu 8 6GnRH-specific probes, found robust GnRH gene expression in the terminal nerve region yet only weak expression in the preoptic area. Comparing the immunocytochemical staining of GnRH neurons by Amano et al (1991) in masu salmon and Bailhache et al (1994) in Atlantic salmon and rainbow trout with in situ labeling in these species shows significantly less labeling in the preoptic area with in situ probes. Indeed, Bailhache et al concluded that this could ''.…”
Section: Surprising Similarity Between 5trp 7 Leu 8 6gnrh In H Burtomentioning
confidence: 93%
“…Anti sGnRH-immunoreactive neurons were smaller than the anti cGnRH ones. The presence of GnRH neurons in the preopticus nucleus has been detected as a sGnRH variant in Cypryniformes (Yu et al, 1988;Powel et al, 1996) and Salmoniformes (Okuzawa et al, 1990;Amano et al, 1991), whereas the cGnRH-II form has been reported in midbrain tegmentum of most of the fish species studied (see Lethimonier et al, 2004 for review). In bluefin tuna, we were able to find weakly immunostained nerve fibres in both the preopticus nucleus and the neurohypophysis.…”
Section: Discussionmentioning
confidence: 99%